2020
DOI: 10.1093/mnras/staa1680
|View full text |Cite
|
Sign up to set email alerts
|

BUDHiES IV: Deep 21-cm neutral Hydrogen, optical, and UV imaging data of Abell 963 and Abell 2192 at z ≃ 0.2

Abstract: ABSTRACT In this paper, we present data from the Blind Ultra-Deep H i Environmental Survey (BUDHiES), which is a blind 21-cm H i spectral line imaging survey undertaken with the Westerbork Synthesis Radio Telescope. Two volumes were surveyed, each with a single pointing and covering a redshift range of 0.164 < z < 0.224. Within these two volumes, this survey targeted the clusters Abell 963 and Abell 2192, which are dynamically different and offer un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 97 publications
0
42
0
Order By: Relevance
“…z ≥ 0.1), there are not many studies of H i emission in galaxies (e.g. Catinella & Cortese 2015;Hess et al 2019;Verheijen et al 2007;Gogate et al 2020). The stellar masses of the galaxies included in such studies are comparable to that of our galaxy, while their H i masses range from 2 × 10 9 M to a few times 10 10 M , considerably greater than the H i mass of our galaxy.…”
Section: Comparison With Galaxies Observed In H I Emission In the Local Universe And Beyondmentioning
confidence: 59%
See 1 more Smart Citation
“…z ≥ 0.1), there are not many studies of H i emission in galaxies (e.g. Catinella & Cortese 2015;Hess et al 2019;Verheijen et al 2007;Gogate et al 2020). The stellar masses of the galaxies included in such studies are comparable to that of our galaxy, while their H i masses range from 2 × 10 9 M to a few times 10 10 M , considerably greater than the H i mass of our galaxy.…”
Section: Comparison With Galaxies Observed In H I Emission In the Local Universe And Beyondmentioning
confidence: 59%
“…There have also been extensions of such studies beyond the local universe (e.g. Catinella et al 2008;Catinella & Cortese 2015;Verheijen et al 2007;Hess et al 2019;Bera et al 2019;Blue Bird et al 2020;Gogate et al 2020). How-ever, even with very deep integrations, direct detections of H i in emission have so far been from gas-rich, star-forming galaxies (≥2 × 10 9 M ; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, H i studies of the environmental impact on galaxies in clusters have been limited to targeted surveys of galaxies based on their optical properties, typically late-type galaxies, for example, studies of the Virgo cluster (Warmels 1988;Cayatte et al 1990Cayatte et al , 1994Chung et al 2009), Abell 262 (Bravo-Alfaro et al 1997), the Coma cluster (Bravo-Alfaro et al 2000, Ursa Major (Verheijen & Sancisi 2001), and Abell 2670 (Poggianti & van Gorkom 2001). In some cases, volume-limited surveys provide a more complete picture such as studies of the Hydra cluster (McMahon 1993), Hercules cluster (Dickey 1997), Abell 2218(Zwaan et al 2001, Abell 496, Abell 754, Abell 85 (Van Gorkom et al 2003), Abell 370 (Lah et al 2007), Abell 963 and Abell 2192 (Verheijen et al 2007; Gogate et al 2020), the ALFALFA Virgo cluster survey (Kent et al 2008), the Antlia cluster (Hess et al 2015) and the Fornax cluster (Loni et al 2021). These studies have provided some insight into the environmental effects on the H i content of cluster galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the observing time required to detect H i beyond z > 0.1 is high. The Blind Ultra Deep H i Environmental Survey (BUDHIES; Gogate et al, 2020) of Abell 963 (A963) and Abell 2192 (A2192) using the Westerbork Synthesis Radio Telescope (WSRT) consists of two deep pointings, 117 × 12 hours on clusters Abell 963, and 72 × 12 hours on Abell 2192 which resulted in 166 galaxies detected in H i over the redshift range 0.164 < z < 0.224. Targeting a higher redshift cluster, Abell 370 (A370) at z = 0.37, used 63 hours of telescope time with the Giant Metrewave Radio Telescope (GMRT) but did not detect any galaxies in H i.…”
Section: H I In Clustersmentioning
confidence: 99%
“…This highlights the need for wide-area H i cluster surveys. A number of blind H i surveys covering galaxy clusters have already been published Lah et al, 2007;Kent et al, 2008;Gogate et al, 2020) with more that are planned or currently being observed by MeerKAT, the Australian SKA Pathfinder (ASKAP) telescope, and Apertif on the Westerbork Synthesis Radio Telescope. In this chapter, I present a blind H i survey of Abell 2626 observed with MeerKAT.…”
Section: Introductionmentioning
confidence: 99%